2009
DOI: 10.1007/s00247-009-1434-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimated cumulative radiation dose from PET/CT in children with malignancies: a 5-year retrospective review

Abstract: BackgroundThe increasing use of serial PET/CT scans in the management of pediatric malignancies raises the important consideration of radiation exposure in children.ObjectiveTo estimate the cumulative radiation dose from PET/CT studies to children with malignancy and to compare with the data in literature.Materials and methodsTwo hundred forty-eight clinical PET/CT studies performed on 78 patients (50 boys/28 girls, 1.3 to 18 years old from December 2002 to October 2007) were retrospectively reviewed under IRB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(106 citation statements)
references
References 12 publications
2
95
1
5
Order By: Relevance
“…However, the dose from PET alone contributed to less than a quarter of the total dose from PET/ CT (3). A retrospective review of 78 pediatric patients with cancer also demonstrated that the average effective doses from CT, PET, and PET/CT were 20.3 mSv, 4.6 mSv, and 24.8 mSv, respectively (18). In this study, the average effective dose from PET was 3.44 mSv, comparable with previous results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the dose from PET alone contributed to less than a quarter of the total dose from PET/ CT (3). A retrospective review of 78 pediatric patients with cancer also demonstrated that the average effective doses from CT, PET, and PET/CT were 20.3 mSv, 4.6 mSv, and 24.8 mSv, respectively (18). In this study, the average effective dose from PET was 3.44 mSv, comparable with previous results.…”
Section: Discussionsupporting
confidence: 88%
“…The reported radiation dose from standard PET/ CT with diagnostic contrast-enhanced CT and CT topography was 21 mSv for a 55 kg 15-year-old, 18 mSv for a 20 kg five-yearold, and 15 mSv for a 10 kg one-year-old child (17). Moreover, the cumulative radiation dose from PET/CT per patient has been reported to be up to 399 mSv (18). However, the dose from PET alone contributed to less than a quarter of the total dose from PET/ CT (3).…”
Section: Discussionmentioning
confidence: 99%
“…55 Furthermore, repeated PET scans increase the radiation exposure and thereby increase the risk for malignancy. 56 The high rate of false-positive results highlights the importance of a confirmatory tissue biopsy. Even in patients with positive findings on interim PET, histologic confirmation plays an important role in identifying true relapse.…”
Section: Screening For Relapsementioning
confidence: 99%
“…Recent studies suggest that radiation exposure in childhood, especially by CT, bears the risk of negative long-term effects including secondary malignancies [40,41]. In contrast to adult oncologic patients, pediatric patients often have an excellent long-term prognosis [42] and receive numerous follow-up examinations with significant cumulative radiation exposure [43]. In this context, the use of PET/ MRI enables a significant reduction of cumulative doses.…”
mentioning
confidence: 99%